2018
DOI: 10.1264/jsme2.me17143
|View full text |Cite
|
Sign up to set email alerts
|

Different Metabolomic Responses to Carbon Starvation between Light and Dark Conditions in the Purple Photosynthetic Bacterium, <i>Rhodopseudomonas palustris</i>

Abstract: Purple photosynthetic bacteria utilize light energy for growth. We previously demonstrated that light energy contributed to prolonging the survival of multiple purple bacteria under carbon-starved conditions. In order to clarify the effects of illumination on metabolic states under carbon-starved, non-growing conditions, we herein compared the metabolic profiles of starved cells in the light and dark using the purple bacterium, Rhodopseudomonas palustris. The metabolic profiles of starved cells in the light we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 36 publications
3
6
0
Order By: Relevance
“…We found that although light-incubated cells maintained high levels of intracellular ATP over a period of 25 d following growth arrest, ATP levels dropped to undetectable levels over the same period in dark-incubated cells. These results are in line with those obtained with the same strain of R. palustris (CGA009) by Kanno et al(20) In addition, these investigators measured the adenylate energy charge ([ATP] + 0.5 [ADP])/[ATP] + [ADP] + [AMP]) (21) of light and dark-incubated cells at day 5 post-growth arrest and found that whereas the energy charge of light-incubated cells matched that of growing cells, the energy charge of dark-incubated cells was dramatically lower. We note that intracellular ATP levels dropped in advance of losses of viability, suggesting that energy depletion caused cell death.…”
Section: Discussionsupporting
confidence: 93%
“…We found that although light-incubated cells maintained high levels of intracellular ATP over a period of 25 d following growth arrest, ATP levels dropped to undetectable levels over the same period in dark-incubated cells. These results are in line with those obtained with the same strain of R. palustris (CGA009) by Kanno et al(20) In addition, these investigators measured the adenylate energy charge ([ATP] + 0.5 [ADP])/[ATP] + [ADP] + [AMP]) (21) of light and dark-incubated cells at day 5 post-growth arrest and found that whereas the energy charge of light-incubated cells matched that of growing cells, the energy charge of dark-incubated cells was dramatically lower. We note that intracellular ATP levels dropped in advance of losses of viability, suggesting that energy depletion caused cell death.…”
Section: Discussionsupporting
confidence: 93%
“…As reported by Kanno et al. (55), the photosynthetic units are not disassembled in the dark, even under starvation. These are readily available, once the light conditions are restored, to produce ATP and NADH for the biosynthetic processes.…”
Section: Acetate Rather Than Light Drives the Metabolic Responses Of supporting
confidence: 56%
“…ATP is an essential energy source in the metabolic activities including photosynthesis of R. palustris, and the ATP synthesis is attributed to the increased generation of proton gradient . ATP production efficiency of R.…”
Section: Resultsmentioning
confidence: 99%
“…ATP is an essential energy source in the metabolic activities including photosynthesis of R. palustris, and the ATP synthesis is attributed to the increased generation of proton gradient. 43 ATP production efficiency of R. palustris was also studied to further prove the effect of R. palustris/CPNs-TAT on the photosynthesis of R. palustris. The ATP production of R. palustris in the presence of CPNs-TAT was measured by ATP kit.…”
Section: Resultsmentioning
confidence: 99%